2016
DOI: 10.17159/sajs.2016/20150058
|View full text |Cite
|
Sign up to set email alerts
|

Responses of African elephants towards a bee threat: Its application in mitigating human–elephant conflict

Abstract: Human settlement expansion into elephant ranges, as well as increasing elephant populations within confined areas has led to heightened levels of human–elephant conflict in southern African communities living near protected areas. Several methods to mitigate this conflict have been suggested including the use of bees as an elephant deterrent. We investigated whether bee auditory and olfactory cues (as surrogates for live bees) could be used to effectively deter elephants. We evaluated the responses of elephant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…These findings are in line with studies describing African elephants to exhibit freezing and slow retreat behaviors when confronted with African bees (King, Douglas‐Hamilton, & Vollrath, 2007; Ndlovu, Devereux, Chieffe, Asklof, & Russo, 2016), both indicators of subordination (De Silva, Schmid, & Wittemyer, 2017). Other exhibited attentive or alarmed behaviors were the spreading of ears (expression of alarm, excitement or surprise, Poole & Granli, 2009), flapping ears (Ndlovu et al, 2016), tail in the air (fearful, playful or excitement, Poole & Granli, 2009). As bee stings are especially painful up the trunk, around the eyes and behind the ears (King, 2019), we specifically looked for behavior that would indicate elephants protecting these sensitive areas.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are in line with studies describing African elephants to exhibit freezing and slow retreat behaviors when confronted with African bees (King, Douglas‐Hamilton, & Vollrath, 2007; Ndlovu, Devereux, Chieffe, Asklof, & Russo, 2016), both indicators of subordination (De Silva, Schmid, & Wittemyer, 2017). Other exhibited attentive or alarmed behaviors were the spreading of ears (expression of alarm, excitement or surprise, Poole & Granli, 2009), flapping ears (Ndlovu et al, 2016), tail in the air (fearful, playful or excitement, Poole & Granli, 2009). As bee stings are especially painful up the trunk, around the eyes and behind the ears (King, 2019), we specifically looked for behavior that would indicate elephants protecting these sensitive areas.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, we observed elephants closing their eyes, putting their trunk in their mouth, and flapping their ears when attempting a fence break. Interestingly, our study showed that only 1.1% of the elephants responded to the bees with headshaking, which seems to be a more common reaction to bees in African elephants (King et al, 2007; Ndlovu et al, 2016; Soltis, King, Douglas‐Hamilton, Vollrath, & Savage, 2014). However, our results are in line with the findings of a study in Sri Lanka that showed that none of the Asian elephants expressed head shaking as a response to bees (King et al, 2018).…”
Section: Discussionmentioning
confidence: 66%
“…The retreat response is an output of a trade-off between the advantages of the response (risk-avoidance) versus the costs (less time for beneficial activities such as feeding) [ 4 ]. In the case of the sound of bees, the elephants consistently retreat to this acoustic stimulus as they associate it with the risk of stinging [ 20 , 32 , 36 , 37 ]. In the case of human voices, elephants are more likely to retreat to Maasai men voices as they associate it with a higher threat [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, such hives can be pushed over or broken by advancing elephants and may only be effective if the hive has high levels of bee activity (Vollrath and Douglas-Hamilton 2002;Ngama 2016). For these reasons, the effects of beehive fences may be short term (Nair and Jayson 2016) or perhaps even ineffective (Ndlovu et al 2016). That being said, beehive fences have been found to deter elephants in study sites where there is sustained engagement from non-governmental organizations such as in Laikipia County, Kenya (see King et al 2009King et al , 2011.…”
Section: Discussionmentioning
confidence: 99%